Boundaries Are Blurred: Wild Food Plant Knowledge Circulation across the Polish-Lithuanian-Belarusian Borderland - Julia Prakofjewa; Matteo Sartori; Povilas Šarka; Raivo Kalle; Andrea Pieroni; Renata Sõukand (Biology, 2023)
The circulation of local ecological knowledge (LEK) is a promising avenue of research for wild plant studies. To encourage the acceptance, celebration, and appreciation of biocultural diversity, which is rapidly disappearing nowadays, we need to estimate and assess multifaceted local ecological knowledge. It has direct application for local communities in informing effective policies for improving food security and building community-specific responses to environmental and social transitions. The present study draws on data collected among two ethnic groups—Lithuanians and Poles—via 200 semi-structured in-depth interviews and participant observation conducted in 2018 and 2019 in Podlasie Voivodeship (Poland), the Vilnius Region (Lithuania), and the Hrodna Region (Belarus). We aimed to observe LEK circulation in the border area through cross-ethnic and cross-country comparisons. A total of 2812 detailed use reports of wild plants were recorded. In total, 72 wild plant taxa belonging to 33 plant families were used across the food domain. Our findings show that cross-country differences were minimal, while there was some variation between the ethnic groups selected as case studies. We emphasize the need, in future studies, to combine quantitative research with qualitative approaches in order to more thoroughly identify peculiarities of cross-border circulation as a reservoir for community food resilience and biocultural diversity.